The importance of socioeconomic status in the occurrence of mental health problems in 11- to 17year-old girls and boys in Germany : results of KiGGS wave 2 (2014-2017) - Maren Theresa Christin Fendt; Heike Hölling; Thomas Lampert; Julia Waldhauer (Das Gesundheitswesen, 2023)
Aim of the study The aim of the study was to investigate the distribution pattern of mental health problems (emotional problems, conduct problems, peer problems, hyperactivity) among different socioeconomic groups of 11- to 17-year-old girls and boys. Methods Data for this study were obtained from the German Health Interview and Examination Survey for Children and Adolescents KiGGS Wave 2 (2012-2014, n=15,023). The data on 11- to 17-year-old girls and boys (n=6599) was analyzed overall and separately for two age groups. The dependent variable was the parental version of the Strengths and Difficulties Questionnaire (SDQ). As non-dependent variable, a multidimensional index was used, which indicates the socioeconomic status (SES) of the family. Prevalence and odds ratios (ORs) based on logistic regressions are shown. Results The prevalence of reporting mental health problems in those aged 11 to 17 was 15.7%. Girls were more likely to show internalizing problems whilst boys were more likely to show externalizing problems. The 11- to 17-year-old adolescents with a low SES were about two times (aOR: 2.32; 95%-CI: 1.81-2.97; p<0.001) more likely to report mental health problems. Adolescent girls with a low SES were at a twofold (aOR: 2.06; 95%-CI: 1.49-2.98; p<0.001) increased risk of showing a specific mental health problem such as emotional problems.Conclusion Mental health problems in adolescents are distributed unequally. 11- to 17-year-old boys are generally more likely to show mental health problems, while girls' SES differences in mental health are more pronounced.
Keywords: Adolescents; Health Inequalities; KiGGS; Mental Health Problems; Social Inequalities; Strengths and Difficulties Questionnaire (SDQ)